Associações entre, índices fisiológicos e fadiga neuromuscular com padrões de deslocamento e desempenho do chute de finalização no futsal - Milioni, Fabio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of the present study was to investigate possible associations between physiological and neuromuscular parameters with time-motion patterns and performance of shooting in futsal. Three studies were performed. In studies 1 and 2, amateur futsal athletes performed the Running Anaerobic Sprint Test (RAST) and the lactate minimum protocol. On different days participated in two simulated games of futsal. During the games the blood lactate concentrations ([Lac]), perceived exertion (RPE) and heart rate (HR) were monitored and recorded for subsequent tracking of time-motion players. In study 3, professional futsal athletes performed an incremental test for determining the anaerobic threshold and maximal oxygen uptake. Then was performed three simulated games monitored for [Lac] and HR and recorded entirely for later tracking of the time-motion players. Neuromuscular parameters were evaluated by surface electromyography, maximal isometric voluntary contractions and the Twitch Interpolation Technique. For statistical analysis were used Student's t test for dependent samples, ANOVA - one way and Pearson’s correlation test to investigate possible associations between the variables investigated. The significance level was assumed as 95% in all cases. Were verified positive associations of aerobic indexes, with the performance during repeated sprints, the energy contribution of alactic system and variables from the tracking, despite a significant drop in performance of time-motion analysis and neuromuscular parameters, has not been verified decrease in performance of the finishing kicks. These results highlight the need for development of the aerobic system for amateur futsal players to mitigate the drop in performance, however it is likely that for higher level players, neuromuscular factors are determinants during intermittent high-intensity efforts. Furthermore, the fall of neuromuscular performance, although it affects the time-motion...

O objetivo do presente estudo foi investigar as possíveis associações entre parâmetros fisiológicos e neuromusculares, com padrões de deslocamento e o desempenho do chute de finalização no futsal. Para isso foram realizados 3 estudos. Nos estudos 1 e 2, atletas amadores de futsal realizaram o Running Anaerobic Sprint Test (RAST) e o Protocolo de Lactato Mínimo. Em diferentes dias participaram de dois jogos de futsal simulados. Durante os jogos as concentrações sanguíneas de lactato ([Lac]), percepção subjetiva de esforço (PSE) e frequência cardíaca (FC) foram monitoradas, e as simulações filmadas para posterior rastreamento do deslocamento dos jogadores. No estudo 3, atletas profissionais de futsal realizaram teste incremental para a determinação do limiar anaeróbio e consumo máximo de oxigênio. Em seguida foram realizados três jogos simulados monitorados quanto à [Lac] e FC e filmados integralmente para posterior rastreamento do deslocamento dos jogadores. Os parâmetros neuromusculares foram avaliados por meio da eletromiografia de superfície, contrações isométricas voluntárias máximas e da utilização da técnica de Twitch Interpolation. Para análise estatística foram utilizados testes t de Student para amostras dependentes, análise de variância ANOVA - one way, além de Correlações de Pearson para verificação de possíveis associações entre as diversas variáveis investigadas. O nível de significância foi assumido como 95% em todos os casos. Foram verificadas associações positivas dos índices aeróbios, com o desempenho durante sprints repetidos, contribuição energética do sistema alático e variáveis provenientes do rastreamento e apesar de queda significativa da performance dos padrões de deslocamento e dos parâmetros neuromusculares, não foi verificado diminuição do desempenho dos chutes de finalização. Tais resultados evidenciam a necessidade de desenvolvimento do sistema aeróbio...
Keywords: Fisiology; Fisiologia; Capacidade aeróbia; Aptidão física do atleta; Biomecânica; Transmissão neuromuscular; Jogadores de futebol; Fadiga; Futebol de salão